Hakikat Pendidikan Islam Dalam Surat Al-Jumu’ah Ayat 2 Telaah Tafsir Tarbawi tentang Tilawah, Tazkiyah, dan Ta’lim - Lailatul Choiriyah; Achmad Saifu Dzulfiqar; Dhini Dwi Fitriani; Ahmad Yusam Thobroni (Edu Berkah Khatulistiwa, 2026)
The learning process can achieve success when it is aligned with the essence of education as explained in the Qur'an. However, in practice, educational institutions are still found that are not grounded in Qur'anic learning standards, resulting in a less-than-optimal learning process that fails to achieve its objectives. This study aims to analyze the essence of Islamic education in Surah Al-Jumu'ah, verse 2, through a conceptual-normative tafsir tarbawi (educational interpretation) approach. This research employs a library research method, with the Qur'an and tafsir literature as its primary sources, supported by contemporary Islamic education studies. The findings indicate that the structure of this verse encompasses three main pillars of Islamic education: Tilawah (recitation), Tazkiyah (purification), and Ta’lim (teaching), which are arranged systemically and integratively. Tilawah functions as an epistemological foundation, affirming revelation as a source of knowledge; Tazkiyah plays a role in the moral-spiritual transformation process for character building; while Ta’lim serves as the mechanism for systematizing knowledge and wisdom in the learning process. The integration of these three pillars forms a holistic Islamic educational paradigm oriented towards tawhid (monotheism) and free from the dichotomy between religious and general sciences. This study affirms that QS. Al-Jumu'ah: 2 not only represents the prophetic mission but also serves as a normative blueprint for developing a transformative and civilized curriculum and system for Islamic education.